Uncovering Violence Occurring in Dating Relationsip: An Early Study Of Forgiveness Approach - Christina Pattiradjawane; Sutarto Wijono; Jacob Daan Engel (PSIKODIMENSIA, 2019)
Violence towards women in the personal realm continues to occur in all provinces in Indonesia. The phenomenon of violence in the personal realm is experienced more by women due to fear, guilt, shame, and feeling that they have no support socially or individually. This study aims to determine the forgiveness approach as a form of recovery for women who experience violence in the personal realm. This research is a theoretical study using secondary data. The results of this theoretical study show that victims who experience violence can be recovered through forgiveness approach to express forgiveness for perpetrators. Forgiveness can be done because the victims have motivation not to avoid and respond to acts of violence perpetrated by the perpetrators, and even continues to be motivated to do good things. If forgiveness is done sincerely, it can make easier for the victims to forgive themselves and others, otherwise forgiveness is difficult to do totally if the victims choose to take revenge and avoid the perpetrators.